Introducing enteral feeding induces intestinal subclinical inflammation and respective chromatin changes in preterm pigs. (June 2015) - Willems, Rhea; Krych, Lukasz; Rybicki, Verena; Jiang, Pingping; Sangild, Per T; Shen, René L; Hensel, Kai O; Wirth, Stefan; Postberg, Jan; Jenke, Andreas C
Aim: To analyze how enteral food introduction affects intestinal gene regulation and chromatin structure in preterm pigs.Materials & methods: Preterm pigs were fed parenteral nutrition plus/minus slowly increasing volumes of enteral nutrition. Intestinal gene-expression and chromatin structure were analyzed 5 days after birth.Results: Enteral feeding led to differential upregulation of inflammatory and pattern recognition receptor genes, including IL8 (median: 5.8, 95% CI: 3.9–7.8 for formula; median: 2.2, 95% CI: 1.3–3.3 for colostrum) and TLR4 (median: 3.7, 95% CI: 2.6–4.8 for formula; no significant differences for colostrum) with corresponding decondensed chromatin configurations. On histology this correlated with mild mucosal lesions, particularly in formula-fed pigs. In CaCo-2 cells, histone hyperacetylation led to a marked increase in TLR4 mRNA and increased IL8 expression upon stimulation with lipopolysaccharide (median: 7.0; interquartile range: 5.63–8.85) compared with naive cells (median 4.2; interquartile range: 2.45–6.33; p = 0.03).Conclusion: Enteral feeding, particular with formula, induces subclinical inflammation in the premature intestine and more open chromatin structure in key inflammatory genes. This may increase the susceptibility for necrotizing enterocolitis.